The relationship between firm digital transformation, green transformation and risk taking: A review of the underpinning theories - Juan, Wang; Kharuddin, Khairul Ayuni Mohd; Ismail, Rina Fadhilah (Edelweiss Applied Science and Technology, 2025)
The growth of the green and digital economy has encouraged businesses to undergo both green and digital transformations. Consistently, research on how risk-taking is affected by a firm’s digital and green transformations has grown significantly. This paper analyzes the relevant theories that explain how digital transformation and green transformation affect firm risk-taking. A review of the literature highlighted that agency theory, information asymmetry theory, and resource-based theory are the three main theories used in existing research to explain the relationship between firm digital and green transformations and firm risk-taking. According to agency theory, firm digital transformation and green transformation can alleviate agency problems and promote firm risk-taking. The information asymmetry theory states that digital and green transformation increases a firm’s information transmission efficiency, which encourages firm risk-taking. The resource-based theory asserts that digital transformation and green transformation provide firms with effective resources and promote risk-taking. These three theories have examined the relationship between risk-taking, green transformation, and firm digital transformation from various angles, offering concepts and insights into the financial effects of these changes, as well as theoretical support for future studies.